Influence of organic binder and moisture content on the durability of rice husk and rice straw-based pellets - Zulkornain, Muhammad Fikri; Mohd Rawian, Nur Adilah; Neshaeimoghaddam, Hesam; Shamsuddin, Abd Halim; Md Saad, Juniza; Abd Rahman, Adlansyah; Samsuri, Shafirah; Naning, Fatin Hana (Chaoyang University of Technology, 2022)
Biomass can partly replace or reduce coal consumption in power generation, hence reducing the agricultural waste disposal issues and environmental pollution generated by fossil fuel emissions. Pelletization is among the techniques for utilizing biomass and has the advantage of being low cost and easy handling. In this research, broken rice was used as an organic binder at 5%, 10% and 15% and three different moistures (14%, 17% and 20%) were applied for rice husk and rice straw-based pellet, and the evaluation of pellet durability has been conducted. The results show that the addition of broken rice as a pellet binder significantly improves biomass pellet durability. The highest durability of rice husk-based pellet achieved was 99.4% with the binder addition of only 10%. For rice straw-based pellet, the binder percentage is directly proportional to pellet durability up to 15% of binder addition. The result shows a similar trend for the effect of moisture on pellet durability. For rice husk-based pellet, the optimal moisture addition is 17%, while for rice straw-based pellet, the durability increased as the moisture increased with the highest durability of 98.9% at 20% moisture addition. Rice straw requires more binder and moisture to enhance the pellet durability because raw rice straw contains less natural lignin and cellulose content than rice husk.